2023
DOI: 10.2478/mgr-2023-0012
|View full text |Cite
|
Sign up to set email alerts
|

Compact and polycentric urban forms as intertwined concepts: Learning from the impacts of Covid–19 retail restrictions on spatial (in)equalities in Brno (Czech Republic)

Marek Lichter,
Jiří Malý

Abstract: Urban structure conceptualisation using compact and polycentric city narratives is often performed separately. However, although both are based on different spatial grammars, they are inextricably linked. The spatially equitable distribution and accessibility of urban functions are often seen as their main contributions. This paper uses the unprecedented circumstances of the COVID-19 pandemic to further analyse the relationship between the two narratives, using the radical transformation of a retail network in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The results do not indicate significant changes and these results might indicate the good accessibility of conventional shops in general (as Table 6 shows). However, Lichter and Malý ( 35 ) found that government restrictions had different impacts on (not only) food purchase accessibility in cities, depending on the various types of urban structure that implies diverse forms and assortment of retail units. Thus, the authors argue that more comprehensive retail planning that reflects the potential local impacts of global crises is essential to ensure greater spatial equity in access to basic daily commodities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results do not indicate significant changes and these results might indicate the good accessibility of conventional shops in general (as Table 6 shows). However, Lichter and Malý ( 35 ) found that government restrictions had different impacts on (not only) food purchase accessibility in cities, depending on the various types of urban structure that implies diverse forms and assortment of retail units. Thus, the authors argue that more comprehensive retail planning that reflects the potential local impacts of global crises is essential to ensure greater spatial equity in access to basic daily commodities.…”
Section: Resultsmentioning
confidence: 99%
“…Related to retail landscapes and consumer behavior, the very dynamic processes were shaped by internationalization trends and the adoption of Western models and patterns of shopping behavior ( 34 ) leading to the enormous spread of foreign retail companies in the form of large-scale retail formats (such as hypermarkets, supermarkets, discount stores and shopping malls) and causing a radical transformation of retail networks in post-socialist cities ( 35 ). Therefore, transnational corporations have gained dominance, and partially replaced traditional smaller retail facilities ( 36 , 37 ).…”
Section: Specific Situation Of the Agri-food System And Afns In Czechiamentioning
confidence: 99%